PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP KEPUASAN KONSUMEN PADA AZKO LP PURI PX - Nur Siam Apriyanto; Nurmin Arianto (Jurnal Publikasi Manajemen Informatika, 2026)
Increasingly fierce competition in the retail business has prompted companies to improve service quality and strengthen promotional strategies in order to maintain customer satisfaction and loyalty. This study aims to analyse the influence of service quality and promotions on customer satisfaction at Azko LP Puri PX. The research method employs a quantitative approach using descriptive associative techniques, with a population of all customers recorded in December 2023, totaling 9,583 individuals. Data was collected through questionnaires, observations, and interviews, then analysed using multiple linear regression with the assistance of SPSS. The results of the study indicate that service quality has a positive and significant impact on customer satisfaction, while promotions also have a positive impact, though to a lesser extent than service quality. Simultaneously, both variables have a significant impact, contributing 69.2% to customer satisfaction. These findings confirm that improving service quality is a dominant factor in building customer satisfaction and loyalty, while promotions remain important in supporting the company's appeal amid market competition.